Fatal Exsanguination Following Rupture of an Iliac Artery Aneurysm in an Infant With Menkes Disease. (October 2019) - Ng, Rachel; Eliezer, Dilharan; Vilain, Ricardo; Kamien, Benjamin; Deshpande, Aniruddh V
Menkes disease (MD) usually presents in infancy with respiratory and neurological complications. Severe isolated vasculo-connective tissue involvement in infancy is rare, and hence the precise and timely diagnosis is difficult. We report a case of an 8-week-old male infant who succumbed to acute, severe exsanguination, and hemorrhagic shock secondary to a large retroperitoneal hematoma due to rupture of a right iliac artery aneurysm. Perimortem musculoskeletal findings raised suspicion of nonaccidental injury. However, postmortem review of facial traits raised the suspicion of MD. MD was subsequently confirmed on genetic testing. Child health clinicians must remain aware of MD as a rare cause of infant vasculopathy or atypical skeletal abnormalities.